2004
DOI: 10.1029/2003wr002750
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of non‐Fickian transport in geological formations with multiple‐scale heterogeneities

Abstract: [1] We develop a numerical method to model contaminant transport in heterogeneous geological formations. The method is based on a unified framework that takes into account the different levels of uncertainty often associated with characterizing heterogeneities at different spatial scales. It treats the unresolved, small-scale heterogeneities (residues) probabilistically using a continuous time random walk (CTRW) formalism and the largescale heterogeneity variations (trends) deterministically. This formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 51 publications
1
119
0
Order By: Relevance
“…This is however inconsistent with the experimental evidence [1], where the solute transported in the F→C direction is observed to arrive faster with respect to the one transported in the C→F direction. Similarly, the adoption of a Fokker-Planck (FP) constitutive relationship j in [14] predicts faster solute arrival times are for the C→F flow direction and thus does not explain the results in [1].…”
mentioning
confidence: 99%
“…This is however inconsistent with the experimental evidence [1], where the solute transported in the F→C direction is observed to arrive faster with respect to the one transported in the C→F direction. Similarly, the adoption of a Fokker-Planck (FP) constitutive relationship j in [14] predicts faster solute arrival times are for the C→F flow direction and thus does not explain the results in [1].…”
mentioning
confidence: 99%
“…The average normalised flux concentration of chloride, j at the outlet of the apparatus (bold points) vs. time/min. It also shows the best ADE (dotted line) and CTRW fit (see section 3.2) (bold line) for these results by Cortis et al (2004). They show clearly that using the ADE gave poor predictions of the early and late time periods that is characteristic of anomalous transport.…”
Section: Pore-scale Dispersionmentioning
confidence: 96%
“…The CTRW formulation has not only reproduced field scale numerical models as discussed earlier in the report (c.f. section 3.2 paragraph 2) but has been successful in simulating tracer migration in several field/laboratory scale experiments (Berkowitz and Scher , 1998;Berkowitz et al, 2000;Kosakowski et al, 2001;Levy and Berkowitz , 2003;Cortis et al, 2004), as described in section 3.1. In summary, each study demonstrated non-Gaussian dispersion that is typical in porous systems, showed it could not be modelled using traditional average approaches and then applied CTRW theory coupled with an appropriate ψ(t) to reproduce the given results.…”
Section: Comparison With Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are commonly referred to as unresolved heterogeneities and are typically accounted for in modeling through the use of dispersion parameters. Also, these features have been suggested as possible contributors to anomalous transport behavior and preferential flow path formation [5,9,10,25,45]; however, the precise influence of these heterogeneities is largely unknown. Many of the software packages currently available for heterogeneity modeling [e.g., Geostatistical Software Library (GSLIB), FLUVSIM, and transition probability geostatistics (TPROGS)] do not account for process-based geologic tendencies and rely on oversimplifications of subsurface geometry [4].…”
Section: Introductionmentioning
confidence: 98%